2007
DOI: 10.14704/nq.2006.4.2.96
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Consciousness and Panpsychism: A Solution to the Hard Problem

Abstract: We analyze the results and implications of the combination of quantum and consciousness. The quantum effect of consciousness is first explored. We show that the consciousness of the observer can help to distinguish the definite states and their quantum superposition, while the usual physical measuring device without consciousness can not do. The result indicates that the causal efficacies of consciousness do exist when considering the basic quantum process. Based on this conclusion, we demonstrate that conscio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The quantum information leads again to the conclusion that the interference of cosmology and philosophy might give the complete interpretation of the events occurring in our universe. Furthermore, Gao Shan [27] demonstrated that consciousness is not reducible or emergent, but new fundamental property of matter. This provides a quantum basis for panpscychism.…”
Section: The Scientific Argumentmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantum information leads again to the conclusion that the interference of cosmology and philosophy might give the complete interpretation of the events occurring in our universe. Furthermore, Gao Shan [27] demonstrated that consciousness is not reducible or emergent, but new fundamental property of matter. This provides a quantum basis for panpscychism.…”
Section: The Scientific Argumentmentioning
confidence: 99%
“…The consciousness of the observer is supposed to 'split', so that there is one in each of the worlds for which the observer remains alive and conscious [10]. At present, even if this theory has not been found to be complete, but one thing is certain, i.e the collapse process of wave function is one kind of dynamical process, and it takes a finite time interval between the collapse time tC and the normal conscious time tP and tC > tP was assumed [27]. Shan has demonstrated, the conscious being or the matter with consciousness can recognize the nonorthogonal states, while the usual physical measuring device or matter without consciousness cannot.…”
Section: The Scientific Argumentmentioning
confidence: 99%
“…It would appear that consciousness, as manifested by the capacity to make choices, is to some extent inherent in matter. Similarly, based upon his extensive quantum mechanics experimentation and analysis, Chinese quantum physicist, Shan (2005), claims that “consciousness is not reducible or emergent, but a new fundamental property of matter” (p. 17). Despite what we may wish to believe, science has clearly shown that our physical world is not solid and insentient but largely hollow and sentient.…”
Section: Human Consciousness From a Philosophical Perspectivementioning
confidence: 99%